De novo variants in RNF213 are associated with a clinical spectrum ranging from Leigh syndrome to early-onset stroke - Brunet, Theresa; Zott, Benedikt; Lieftüchter, Victoria; Lenz, Dominic; Schmidt, Axel; Peters, Philipp; Kopajtich, Robert; Zaddach, Malin; Zimmermann, Hanna; Hüning, Irina; Ballhausen, Diana; Staufner, Christian; et al. (Genetics in medicine, 2024)
Purpose - RNF213, encoding a giant E3 ubiquitin ligase, has been recognized for its role as a key susceptibility gene for moyamoya disease. Case reports have also implicated specific variants in RNF213 with an early-onset form of moyamoya disease with full penetrance. We aimed to expand the phenotypic spectrum of monogenic RNF213-related disease and to evaluate genotype-phenotype correlations. - Methods - Patients were identified through reanalysis of exome sequencing data of an unselected cohort of unsolved pediatric cases and through GeneMatcher or ClinVar. Functional characterization was done by proteomics analysis and oxidative phosphorylation enzyme activities using patient-derived fibroblasts. - Results - We identified 14 individuals from 13 unrelated families with (de novo) missense variants in RNF213 clustering within or around the Really Interesting New Gene (RING) domain. Individuals presented either with early-onset stroke (n = 11) or with Leigh syndrome (n = 3). No genotype-phenotype correlation could be established. Proteomics using patient-derived fibroblasts revealed no significant differences between clinical subgroups. 3D modeling revealed a clustering of missense variants in the tertiary structure of RNF213 potentially affecting zinc-binding suggesting a gain-of-function or dominant negative effect. - Conclusion - De novo missense variants in RNF213 clustering in the E3 RING or other regions affecting zinc-binding lead to an early-onset syndrome characterized by stroke or Leigh syndrome.